Evaluation of Antimicrobial Activity and Synergistic Effect of Spices against Few Selected Pathogens (Tribhuvan University Journal of Microbiology, 2019)
Objectives: The main objective of this study was to evaluate antimicrobial activity of ethanolic extract of spices along with determination of its synergistic effect against few selected pathogens.Methods: In this study, ethanolic extract of 5 different spices; Zingiber officinale (Ginger), Allium sativum (Garlic), Curcuma longa (Turmeric), Capsicum annum (Chili) and Allium cepa (Onion) were obtained by using Soxhlet apparatus. The ethanolic extract was concentrated by evaporation and different concentrations of extract were prepared in Dimethy Sulphoxide (DMSO) solvent. Test organisms included mainly pathogens i.e. Escherichia coli, Staphylococcus aureus, Pseudomonas aeruginosa, Klebsiella pneumoniae. The antimicrobial activities of the extracts were determined by well diffusion technique both individually and in combination. On the other hand, Minimum Inhibitory Concentration (MIC) and Minimum Bactericidal Concentration (MBC) was determined by serial dilution technique. The result were interpreted on the basis of the fact that the growth occurs in positive control and other tubes with inadequate amount of extract whereas the lowest concentration of agent that inhibits growth of organism, detected by lack of visible turbidity by inhibition of 99% is designed as the MIC. The MBC is identified by determining the lowest concentration of extract solution that reduces the viability of the initial bacterial inoculum by a predetermined reduction such as ≥99.9%. Likewise, for determination of Fractional Inhibitory Concentration Index (FICI), two extracts were combined along with standardized inoculum of bacterial strain. Tubes without visible turbidity were streaked on agar plate and observed for 99.9% killing.  Results: All the tested extract of spices were found effective against S. aureus and K. pneumoniae only. The highest zone of inhibition (ZOI) was found in chili extract (ZOI=26 mm) against S. aureus whereas lowest zone of inhibition was found in garlic extract against K. pneumoniae (ZOI=12mm). Similarly, highest ZOI was produced by combined extract of both Turmeric and Ginger (ZOI= 26 mm). Turmeric extract was found to be effective against S. aureus (MIC value = 62.5 mg /ml and MBC value = 31.25 mg/ml) and K. pneumoniae (MIC value 125 mg/ml and MBC value = 62.5 mg/ml). The Fractional Inhibitory Concentration (FIC) values of combined extract suggested synergistic and additive effect (0.5